Rekonstruksi Ketidak Adilan Gender Melalui Pendidikan Islam - fahrur rozi (STIU Al-Mujtama Pamekasan, 2019)
Abstract: Discrimination in gender equality is a source of problems in structure of social life and can be caused by patriarchal culture that almost occurs in all walks of life in the world. Considering that, Islam is religion as a rahmatan lil ‘alamin that can be used as a guide for all humanity, it is fitting that Islamic education contributes it to combat gender injustice. Based on the Qur'an and interpretation of gender verses, it is expected to minimize misunderstandings about the true meaning of gender. Keywords: gender injustice, Islamic Education